PEMBERIAN TERAPI KOMPRES HANGAT DENGAN AROMA LAVENDER UNTUK MENURUNKAN NYERI PADA PASIEN POST OPERASI SECTIO CAESAREA : EVIDENCE BASED CASE REPORT (EBCR) (Jurnal Kesehatan Siliwangi, 2023)
Background: Sectio Caesarea is a surgical procedure to deliver a fetus by making an incision to open the abdominal wall and uterine wall or a hysterotomy to remove the fetus in the mother's uterus.Nonpharmacological pain management includes relaxation, hypnosis, positioning and changing, cutaneous, hydrotherapy, hot/cold therapy, music, acupressure, aromatherapy, and techniques of imagining, distraction, and warm compresses with lavender aroma. Purpose: The EBCR aims to determine the effectiveness of warm compress therapy with lavender aroma to reduce pain in postoperative sectio caesarean patients. The benefits of lavender aromatherapy to reduce pain. Method : Searching this journal uses keywords, Boolean Operators and E-data based with. This type of research is literature review and experiment. Results: Provision of lavender aroma warm compresses to post SC patients is proven to reduce the intensity of pain in surgical wounds. Conclusion: Application of warm compresses with lavender aroma can reduce pain intensity in postoperative sectio caesarea patients and relieve pain in stitches.